Richard M. Sudhalter. Lost Chords: White Musicians and Their Contributions to Jazz, 1915-1945. New York: Oxford University Press, 1999. xxii, 890 pp. - Sager, David (Current Musicology, 2001)
Lost Chords: White Musicians and Their Contributions to Jazz, 1915-1945 is fascinating historical criticism, both extremely well written and well re-searched. It is a work that intends to shed light on white and supposedly "forgotten" players of jazz from the pre-bebop era. Its author, Richard M. Sudhalter, sets out to make clear the enormous contributions and talents of these important white musicians. His intention to do so in a balanced way, so as not to cast aspersions on any black musicians, is not wholly successful.